2013
DOI: 10.1177/0022034513501876
|View full text |Cite|
|
Sign up to set email alerts
|

Bis-enoxacin Inhibits Bone Resorption and Orthodontic Tooth Movement

Abstract: Enoxacin inhibits binding between the B-subunit of vacuolar H + -ATPase (V-ATPase) and microfilaments, and also between osteoclast formation and bone resorption in vitro. We hypothesized that a bisphosphonate derivative of enoxacin, bis-enoxacin (BE), which was previously studied as a bone-directed antibiotic, might have similar activities. BE shared a number of characteristics with enoxacin: It blocked binding between the recombinant B-subunit and microfilaments and inhibited osteoclastogenesis in cell cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 24 publications
6
41
0
Order By: Relevance
“…Relatively low systemic doses may allow accumulation of therapeutic doses in the bone. We previously showed that bis-enoxacin inhibits osteoclast activity induced aseptically by mechanical force in a rat orthodontic tooth movement model [24]. The combination of a bone targeted anti-resorptive and antibiotic would seem well-suited for the treatment of PD and our data are consistent with that idea.…”
Section: Discussionsupporting
confidence: 86%
“…Relatively low systemic doses may allow accumulation of therapeutic doses in the bone. We previously showed that bis-enoxacin inhibits osteoclast activity induced aseptically by mechanical force in a rat orthodontic tooth movement model [24]. The combination of a bone targeted anti-resorptive and antibiotic would seem well-suited for the treatment of PD and our data are consistent with that idea.…”
Section: Discussionsupporting
confidence: 86%
“…ALN, a classic nitrogen-containing bisphosphonate, reduced SOS but was less effective than BE. A previous study 23 suggested that BE inhibits osteoclast formation and bone resorption by competitively blocking an interaction between the B2-subunit of V-ATPase and microfilaments. However, it is also known that BE is an antibiotic, which could contribute to its therapeutic effect.…”
Section: Discussionmentioning
confidence: 97%
“…Forty-eight Sprague-Dawley rats were randomly divided into eight groups as follows: 1) polybacterial infection with P. gingivalis, T. denticola, and T. forsythia ; 2) polybacterial infection plus treatment with BE (5 mg · kg −1 · d −1 ); 23 3) polybacterial infection plus treatment with BE (25 mg · kg −1 · d −1 ); 23 4) polybacterial infection plus treatment with ALN (1 mg · kg −1 · d −1 ); 30 5) polybacterial infection plus treatment with ALN (10 mg · kg −1 · d −1 ); 30 6) polybacterial infection plus treatment with ENX (5 mg · kg −1 · d −1 ); 21,23 7) polybacterial infection plus treatment with DOX (5 mg/d); 31 and 8) shaminfected and untreated controls. A daily subcutaneous injection of these treatments was administered for 6 weeks after 6 weeks of initial infection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations